2023
DOI: 10.1039/d3nr00565h
|View full text |Cite
|
Sign up to set email alerts
|

Large area inkjet-printed metal halide perovskite LEDs enabled by gas flow assisted drying and crystallization

Abstract: We demonstrate the upscaling of inkjet-printed metal halide perovskite light-emitting diodes. To achieve this, the drying process, critical for controlling the crystallization of the perovskite layer, was optimized with an...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…We have demonstrated in earlier studies that bright perovskite-based LEDs (PeLEDs) could be frabricated by inkjet printing and upscaled to 1600 mm 2 active area size. 21,22…”
Section: Introductionmentioning
confidence: 99%
“…We have demonstrated in earlier studies that bright perovskite-based LEDs (PeLEDs) could be frabricated by inkjet printing and upscaled to 1600 mm 2 active area size. 21,22…”
Section: Introductionmentioning
confidence: 99%
“…The development of feasible large-area MHP thin lm deposition technology is necessary to realize large areas of PeLED devices. It has been reported that the preparation methods of large-area perovskite lms include blade coating, 18,19 slot-die coating, 20,21 spray coating, 22,23 inkjet printing, 24 and vapor deposition. 25,26 So far, beneting from the improvement of MHP lm quality and the optimization of device structures, large-area PeLEDs have made some important breakthroughs.…”
Section: Introductionmentioning
confidence: 99%
“…Much effort has been made to improve the wettability of the substrate and suppress the coffee ring effect, [44,45] such as solvent engineering for balancing the Marangoni flow and capillary flow [46,47] and interface engineering for adjusting the surface energy. [34,48] However, the EQE of inkjet-printed PeLEDs is still limited to 9.6% with red emission and 13.9% with green emission, [33,49] and the device area is limited to 16 cm 2 [50] ; both still lag behind that of spin-coated or blade-coated PeLEDs on rigid substrates. [21,30] In this work, we demonstrate efficient, flexible, and large-area PeLEDs using inkjet printing.…”
Section: Introductionmentioning
confidence: 99%